If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4m + -120) = 0 Reorder the terms: (-120 + 4m) = 0 Remove parenthesis around (-120 + 4m) -120 + 4m = 0 Solving -120 + 4m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '120' to each side of the equation. -120 + 120 + 4m = 0 + 120 Combine like terms: -120 + 120 = 0 0 + 4m = 0 + 120 4m = 0 + 120 Combine like terms: 0 + 120 = 120 4m = 120 Divide each side by '4'. m = 30 Simplifying m = 30
| -8(r-6)=-8-6(-2+5r) | | -13m+7m=18-66 | | 8.7x=156.6 | | 5x-(3x-2)=18 | | -8x-8=3x+25 | | -8-5(1+6x)=5(1-6x)2x | | -3+a/4=-4 | | V+4-8=6(v+7)+2(v+5) | | 8(x-7)=-112 | | -12-11d=-10d | | ax+bx=-4 | | X=10x-78 | | 3x+4x=6x-8 | | 2x+5+2x-23=90 | | -5+b/8=-4 | | -7(x+3)=3(-5-2x) | | 19=-3+4(v-6) | | 2(x+3)-3x-7=2 | | x+x+x+16=25 | | 7t+6=8t | | x^2+y^2-2xy=144 | | 2a+4b+a-b+10= | | (3xy^3)-3xy=0 | | z(z-i)=iz+2 | | 7x+12=40+3x | | t/9--118=130 | | -7a+1=8(1-a)+1 | | -7b-7=-b-7 | | (2a-6)(3a-15)=0 | | -2(v-882)=162 | | z(z-i)=je+2 | | -18+35+(17)= |